Probability theory and mathematical statistics for engineers - Pugačev, Vladimir S. 1911- (Pergamon Press, 1984)
Probability Theory and Mathematical Statistics for Engineers
Translation of: Teorii͡a veroi͡atnosteĭ i matematicheskai͡a statistika
Includes bibliographical references (pages 439-444) and index
Keywords: MATHEMATICS / Applied; MATHEMATICS / Probability & Statistics / General; Mathematical statistics; Probabilities; Engineering / Statistical methods; Ingenieurwissenschaften